1981
DOI: 10.1007/bf00405906
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on human pharmacokinetics of activated ifosfamide and cyclophosphamide by a modified fluorometric test

Abstract: The activated metabolites of ifosfamide and cyclophosphamide (4-hydroxy-ifosfamide and 4-hydroxy-cyclophosphamide) were analysed fluorometrically by condensation of liberated acrolein with m-aminophenol yielding 7-hydroxyguinoline. Interfering fluorescence of blood and urine was eliminated by extraction with dichlormethane and determination of blanks in which the liberated acrolein reacted with hydrazine to non-fluorescent pyrazoline. The modified test proved effective in identifying low levels of activated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 7 publications
0
29
1
Order By: Relevance
“…urinary concentrations of 4-OH-IF of up to 30 pmol/l were detected [37]: however, these results can not be compared directly with the situation in children receiv ing chemotherapy because the doses applied are higher, and continuous infusions of IF with simultaneous forced diuresis over several days are used. Moreover, no information is available regarding the concentrations of 4-OH-IF in the primary filtrate which the apical membrane of the renal tubule is exposed to or in the interstitial fluid.…”
Section: Discussionmentioning
confidence: 88%
“…urinary concentrations of 4-OH-IF of up to 30 pmol/l were detected [37]: however, these results can not be compared directly with the situation in children receiv ing chemotherapy because the doses applied are higher, and continuous infusions of IF with simultaneous forced diuresis over several days are used. Moreover, no information is available regarding the concentrations of 4-OH-IF in the primary filtrate which the apical membrane of the renal tubule is exposed to or in the interstitial fluid.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, a prolongation in cyclophosphamide elimination half-life will result in a prolongation of the apparent half-life of phosphoramide mustard and probably more importantly that of 4-hydroxycyclophosphamide. Wagner et al (1981) has shown that the apparent half-life of 4-hydroxyifosfamide is approximately 6 h and it would therefore seem likely that the half-life of this metabolite is dependent on the half-life of the parent drug. Thus alteration of the elimination of the half-life of ifosfamide with age may alter the plasma concentration-time profile of the principal metabolite 4-hydroxyifosfamide.…”
Section: Discussionmentioning
confidence: 99%
“…IF and its metabolites are usually determined by classical techniques (fluorimetry, mass spectrometry, chromatography) on derivatized tissue extracts or body fluids (Wagner et al, 1981;Lind et al, 1989;Boddy et al, 1993). More recently however, 31P-MRS has also been used in vitro to follow the metabolism of two other oxazaphosphorine cytostatics, cyclophosphamide and mafosfamide, in cultured tumour cells (Boyd et al, 1980;Sonawat et al, 1990) and to analyse IF metabolities in body fluids from patients Gilard et al, 1993).…”
mentioning
confidence: 99%